In Silico Design of Optimal Dissolution Kinetics of Fe‐Doped ZnO Nanoparticles Results in Cancer‐Specific Toxicity in a Preclinical Rodent Model. Issue 9 (23rd February 2017) - Manshian, Bella B.; Pokhrel, Suman; Himmelreich, Uwe; Tämm, Kaido; Sikk, Lauri; Fernández, Alberto; Rallo, Robert; Tamm, Tarmo; Mädler, Lutz; Soenen, Stefaan J.
Abstract : Cancer cells have unique but widely varying characteristics that have proven them difficult to be treated by classical therapeutics and calls for novel and selective treatment options. Nanomaterials (NMs) have been shown to display biological effects as a function of their chemical composition, and the extent and exact nature of these effects can vary between different biological environments. Here, ZnO NMs are doped with increasing levels of Fe, which allows to finely tune their dissolution rate resulting in significant differences in their biological behavior on cancer or normal cells. Based on in silico analysis, 2% Fe‐doped ZnO NMs are found to be optimal to cause selective cancer cell death, which is confirmed in both cultured cells and syngeneic tumor models, where they also reduce metastasis formation. These results show that upon tuning NM chemical composition, NMs can be designed as a targeted selective anticancer therapy. Abstract : Computational modeling of Fe‐doped ZnO reveals concentration‐ and Fe‐level dependent cancer‐specific toxicity. The optimal formulation is confirmed in various coculture models, giving selective cancer cell death and resulted in a significant reduction in tumor growth. The data reveal the strength of bioinformatics tools in designing an optimal toxic‐by‐design nanoparticle formulation for efficient cancer therapy.